Composite photocatalyst and preparation method thereof

By ball milling TiO2 with graphite to form a composite photocatalyst, the problems of complex preparation and high cost were solved, and the utilization rate of TiO2 for visible light and photocatalytic efficiency were improved.

CN119259019APending Publication Date: 2025-01-07SOUTHWEST UNIVERSITY FOR NATIONALITIES

Patent Information

Application Number
CN202411558347.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing methods for preparing TiO2 composite photocatalysts are complex and expensive, and TiO2 has low utilization of visible light and high recombination rate of photogenerated carriers.

Method used

By ball milling TiO2 particles with graphite, a composite photocatalyst with 2-3 atom carbon layers is formed. The excellent electron transport capacity of graphite is used to improve the separation and transfer efficiency of photogenerated carriers and suppress the recombination of photogenerated electron-hole pairs.

Benefits of technology

It simplifies the preparation process, reduces costs, and improves the absorption and utilization efficiency of visible light, thereby enhancing photocatalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259019A_ABST
    Figure CN119259019A_ABST
Patent Text Reader

Abstract

The invention discloses a composite photocatalyst and a preparation method thereof, and relates to the technical field of photocatalytic functional material synthesis. The preparation method comprises the following steps: mixing TiO2 particles with graphite, and carrying out ball milling treatment to obtain a treated substance; and cleaning the treated object with deionized water, and drying to obtain the composite photocatalyst. The method solves the problems of complexity and high cost of the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis of photocatalytic functional materials, and in particular to a composite photocatalyst and a preparation method thereof. Background Art

[0002] Environmental pollution and energy shortages caused by the development of industrial technology have endangered the living environment of human beings. Semiconductor photocatalytic technology can realize reactions such as water splitting to produce hydrogen, degrading pollutants, and reducing CO2 by converting solar energy into chemical energy, which can provide effective solutions to solve environmental pollution and energy problems. Metal oxide semiconductors such as TiO2 have the characteristics of large band gap, high stability, simple preparation, low cost and high efficiency, and have become one of the hot spots in photocatalyst research. However, the inherent defects of TiO2, such as the large band gap of TiO2 (3.2eV), cause TiO2 to only respond to light in the ultraviolet region, thus the utilization rate of solar energy is very limited; on the other hand, the photogenerated carriers (electron-hole) generated by TiO2 under light excitation are very easy to recombine, resulting in low quantum efficiency and limited catalytic efficiency. In response to these two problems, researchers have used various means to improve the utilization rate of TiO2 for visible light and reduce the recombination rate of photogenerated carriers, including recombination with precious metals (Au, Ag, Pt, etc.), recombination of different semiconductors to form heterojunctions, heterogeneous atom doping, etc.

[0003] Graphene is a two-dimensional material composed of carbon atoms in a hexagonal honeycomb lattice with sp2 hybrid orbitals. It is only one atomic layer thick and has excellent electrical and thermal conductivity, ultra-high electron mobility and ultra-large specific surface area. The composite of graphene and TiO2 can reduce the agglomeration of TiO2 particles, improve the light absorption efficiency, and reduce the recombination of photogenerated electron-hole pairs, thereby improving the photocatalytic activity of TiO2. In current reports, the commonly used methods for composite TiO2 and graphene include sol-gel method, hydrothermal / solvothermal method, in-situ reduction method, electrostatic adsorption method and direct mixing method. Most methods use graphene oxide (GO) as a carbon source, and then reduce the graphene oxide by different means after composite with TiO2 to obtain a graphene / TiO2 composite photocatalyst. The graphene here is actually reduced graphene oxide (rGO). Graphene oxide is a derivative of graphene, which is prepared from graphite by chemical oxidation and exfoliation process. The main difference between graphene oxide and graphene is that its surface and edges contain functional groups with high oxygen content, such as carboxyl (-COOH), hydroxyl (-OH) and epoxy groups, which have poor electrical conductivity. Graphene oxide can be reduced by chemical, thermal or electrochemical methods to remove most of the oxygen-containing functional groups in graphene oxide, thereby restoring some of its structure and properties. The resulting product is called reduced graphene oxide. Compared with the original GO, rGO has significantly improved properties such as electrical conductivity and thermal conductivity. Although it cannot fully achieve the excellent performance of original graphene, its low preparation cost and easy large-scale production make rGO very attractive in practical applications.

[0004] For example, the patent with publication number CN105964236A discloses a method for preparing a graphene / titanium dioxide photocatalyst, which uses a chemical method to prepare graphite oxide, dissolves the obtained graphite oxide in a certain amount of water and ultrasonicates for 1-3 hours to obtain a certain concentration of graphene oxide suspension; 8-13mL of butyl titanate is added to 30-50mL of anhydrous ethanol and 1-3mL of glacial acetic acid under stirring, mixed evenly, and the precursor mixture is slowly dripped into the graphene oxide suspension under stirring, and continued to stir after the addition is complete, and transferred to a reactor with a polytetrafluoroethylene liner for heating reaction, and washed, dried and ground to obtain a solid powder after cooling; the obtained product is roasted in a muffle furnace, taken out and cooled in the air, and ground again to obtain a grayish white sample. However, the preparation method of this patent has the problems of complex method and high cost. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the current method for preparing TiO2 composite photocatalyst is complicated and costly. The purpose is to provide a method for preparing a composite photocatalyst, which solves the problem of complicated preparation method and high cost.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a composite photocatalyst comprises the following steps:

[0008] The TiO2 particles are mixed with graphite and subjected to ball milling treatment to obtain a treated product;

[0009] The treated material is washed with deionized water and dried to obtain a composite photocatalyst.

[0010] As a possible design, the size of the TiO2 particles is 10 to 50 nm.

[0011] As a possible design, the mass ratio of the above-mentioned TiO2 particles to graphite is 1:(1-19).

[0012] As a possible design, the graphite is expanded graphite.

[0013] As a possible design, the ball milling time is 1 to 20 hours.

[0014] As a possible design, grinding balls are added during the ball milling. The grinding balls include small balls, medium balls and large balls. The mass ratio of small balls, medium balls and large balls is (5-7): (2-4): 1. The size of the ball mill jar used for ball milling is 100-150mL.

[0015] As a possible design, the diameter of the large ball is 10 mm, the diameter of the medium ball is 5 mm, and the diameter of the small ball is 2.5 mm.

[0016] As a possible design, the grinding balls are made of zirconium oxide.

[0017] As a possible design, the treated material is washed with deionized water for 3 to 5 times and dried by freeze drying.

[0018] A composite photocatalyst prepared by the method.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0020] The present invention mixes graphite and TiO2 particles and performs ball milling. During the ball milling process, the graphite will evenly wrap 2-3 atomic carbon layers on the surface of the TiO2 particles, the carbon atoms will form CO-Ti bonds with the TiO2, and part of the carbon will exist in the form of graphite carbon. During catalytic degradation, the mobility of electrons on the graphite will be improved, which can improve the separation and transfer efficiency of photogenerated carriers (electrons-holes) in the material, thereby improving the absorption and utilization efficiency of the composite catalyst for visible light, inhibiting the recombination of photogenerated electron-hole pairs generated by TiO2, thereby comprehensively improving the photocatalytic efficiency; in addition, the graphite can also absorb a part of the light, thereby improving the light absorption effect of TiO2.

[0021] The present invention prepares the composite photocatalyst coated with a carbon layer by ball milling. The method is simple and convenient, has low energy consumption, and can keep the TiO2 particle size and lattice structure unchanged without agglomeration and condensation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0023] Figure 1 Scanning electron micrographs of pure TiO2 nanoparticles (a), composite photocatalysts (b) and expanded graphite (c) of Example 1;

[0024] Figure 2 This is a high-resolution transmission electron microscopy image of the composite photocatalyst of Example 1;

[0025] Figure 3 This is an element scanning analysis diagram of the composite photocatalyst of Example 1;

[0026] Figure 4 The UV-visible light absorption spectra of the composite photocatalysts of Examples 1 to 3;

[0027] Figure 5 The photoluminescence spectra of the composite photocatalysts of Examples 1 to 3;

[0028] Figure 6 The photocatalytic degradation diagram of the composite photocatalyst of Examples 1 to 3;

[0029] Figure 7 This is a photocatalytic degradation diagram of the composite photocatalyst of Example 6;

[0030] Figure 8This is a photocatalytic degradation diagram of the composite photocatalyst of Example 7;

[0031] Fig. 9 Thermogravimetric analysis diagrams of the composite photocatalysts of Examples 1 to 3. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0033] Existing methods for preparing TiO2 composite photocatalysts all require doping TiO2 with non-metals, transition metals, rare earth metals, or performing semiconductor composite modification, and the processing methods are complex and costly.

[0034] In view of the above problems, the present invention provides a method for preparing a composite photocatalyst, comprising the following steps:

[0035] S1. Mix TiO2 particles and graphite, and perform ball milling to obtain a processed product.

[0036] When TiO2 particles are ball-milled separately, the TiO2 particles will agglomerate, reducing the specific surface area of ​​the TiO2 particles, thereby affecting the contact area between the TiO2 particles and the reactants, reducing the catalytic reaction rate, and also affecting the particle size and lattice structure of the TiO2 particles. However, the present invention can avoid the agglomeration and condensation of the TiO2 particles by ball-milling the TiO2 particles with graphite, maintain the particle size and lattice structure of the TiO2 particles, and can evenly coat the surface of the TiO2 particles with 2-3 atomic carbon layers. The presence of the carbon layer improves the absorption and utilization efficiency of the composite catalyst for visible light, and the excellent electron transport capacity of the graphite carbon layer improves the separation and transfer efficiency of photogenerated carriers (electrons-holes) in the material.

[0037] Furthermore, the size of TiO2 particles is 10 to 50 nm. The smaller the TiO2 particles are, the larger the specific surface area is, the larger the contact area with the reactants is, the better the reaction is, and the better the corresponding catalytic efficiency is.

[0038] Furthermore, the mass ratio of TiO2 particles to graphite is 1:(1-19).

[0039] Furthermore, the graphite is expanded graphite, flake graphite or graphene oxide. Compared with ordinary graphite, expanded graphite has a larger carbon layer spacing and is easy to peel off. After ball milling, expanded graphite can be coated with TiO2 particles while maintaining a certain lattice structure.

[0040] Furthermore, the ball milling time is 1 to 20 hours.

[0041] Furthermore, grinding balls are added during ball milling, and the grinding balls include small balls, medium balls and large balls, and the mass ratio of small balls, medium balls and large balls is (5-7): (2-4): 1. The size of the ball milling jar used for ball milling is 100-150mL. Since the tangential forces of grinding balls of different sizes are different, the inventors have found that the ball milling effect is better when three grinding balls of different sizes are used for ball milling together. Moreover, ball milling in a ball milling jar of 100-150mL has a better ball milling effect and is more conducive to the graphite being evenly wrapped on the TiO2 particles.

[0042] Furthermore, the mass ratio of the small ball, the medium ball and the large ball is 6:3:1.

[0043] Furthermore, the diameter of the large ball is 10 mm, the diameter of the medium ball is 5 mm, and the diameter of the small ball is 2.5 mm.

[0044] Furthermore, the grinding balls are made of zirconium oxide, which has good wear resistance, low wear rate and low price, and can reduce the preparation cost.

[0045] S2. Wash the treated material with deionized water and dry it to obtain a composite photocatalyst.

[0046] In this step, there is too much graphite wrapped on the surface of the treated object. After cleaning, the excess graphite will remain in the deionized water and can be used for subsequent ball milling, saving preparation costs.

[0047] Furthermore, the treated material is washed with deionized water for 3 to 5 times and dried to be freeze-dried. Freeze-drying can maintain the pore structure, which is convenient for subsequent photocatalytic reaction.

[0048] Example 1

[0049] A method for preparing a composite photocatalyst comprises the following steps:

[0050] TiO2 nanoparticles and expanded graphite were mixed in a mass ratio of 1:3, and ball-milled for 12 hours to obtain a treated product, wherein the mass ratio of small balls, medium balls and large balls used in ball milling was 6:3:1, the total weight of the grinding balls was 200 g, and the size of the ball mill was 125 mL;

[0051] The treated material was washed with deionized water for 5 times and freeze-dried to obtain a light grey powder, which is a composite photocatalyst.

[0052] Reference Figure 1 As shown, (a) is a scanning electron microscope image of pure TiO2 nanoparticles, (b) is a scanning electron microscope image of a composite photocatalyst, and (c) is a scanning electron microscope image of expanded graphite. Figure 1 (a)-(b), the size and structure of TiO2 particles did not change before and after ball milling, which indicates that ball milling of TiO2 nanoparticles and expanded graphite does not lead to agglomeration of TiO2 nanoparticles; Figure 1 (b)-(c), there are no lamellar impurities on the surface of the composite photocatalyst, which indicates that the expanded graphite is broken up during the ball milling process and evenly wrapped on the surface of TiO2 particles, forming CO-Ti bonds with TiO2, and the excess graphite is removed by washing with deionized water.

[0053] Reference Figure 2 As shown, (a) is a high-resolution transmission electron microscopy image of the composite photocatalyst, and (b) is a partial enlarged image of (a). Figure 2 Part (b) clearly shows that there is a thin carbon layer on the surface of the TiO2 nanoparticles. The TiO2 has good crystallinity and a clear lattice, while the lattice structure of the carbon layer on the TiO2 surface is slightly damaged.

[0054] Reference Figure 2-3 It can be seen that the surface of TiO2 particles in the composite photocatalyst is uniformly covered with a carbon layer. The thermal analysis results show that the mass ratio of carbon in the composite photocatalyst is about 2.8%.

[0055] Reference Figure 4 , Figure 4 The black line (TC0) is the UV-visible absorption spectrum of pure TiO2, and the red line (TC1) is the UV-visible absorption spectrum of the composite photocatalyst of Example 1. The UV-visible absorption spectrum can be used to characterize the absorption efficiency of the material to UV-visible light. By comparing the two, it can be seen that the light absorption of the composite photocatalyst of Example 1 in the ultraviolet region is not affected, and the absorption of visible light is significantly enhanced, which indicates that the light absorption effect of the composite photocatalyst after graphite ball milling treatment is improved.

[0056] Reference Figure 5 , Figure 5 The black line (TC0) is the photoluminescence spectrum of pure TiO2, and the red line (TC1) is the photoluminescence spectrum of the composite photocatalyst of Example 1. By comparing the two, it can be seen that the intensity of the radiated light is significantly weakened after the composite photocatalyst is excited, indicating that the carbon layer effectively reduces the recombination of photogenerated carriers and significantly improves the problem of inherent defects of TiO2.

[0057] Example 2

[0058] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of TiO2 nanoparticles to expanded graphite is 1:9.

[0059] A method for preparing a composite photocatalyst comprises the following steps:

[0060] TiO2 nanoparticles and expanded graphite were mixed in a mass ratio of 1:9 and ball-milled for 12 hours to obtain a treated product, wherein the mass ratio of small balls, medium balls and large balls used in ball milling was 6:3:1, the total weight of the grinding balls was 200 g, and the size of the ball mill was 125 mL;

[0061] The treated material was washed with deionized water for 5 times and freeze-dried to obtain a light grey powder, which is a composite photocatalyst.

[0062] The composite photocatalyst of this example was subjected to thermal analysis, and the results of the thermal analysis showed that the mass ratio of carbon in GC / TiO2 was about 1%.

[0063] Reference Figure 4 , Figure 4 The black line (TC0) is the UV-visible absorption spectrum of pure TiO2, and the blue line (TC2) is the UV-visible absorption spectrum of the composite photocatalyst of Example 2. By comparing the two, it can be seen that the light absorption of the composite photocatalyst of Example 2 in the ultraviolet region is not affected, and the absorption of visible light is significantly enhanced, which indicates that the light absorption effect of the composite photocatalyst after graphite ball milling treatment is improved; and by comparing the red line (TC1) and the blue line (TC2), it can be seen that after increasing the amount of graphite added, the light absorption effect of the composite photocatalyst is not significantly increased.

[0064] Reference Figure 5 , Figure 5 The black line (TC0) is the photoluminescence spectrum of pure TiO2, and the blue line (TC2) is the photoluminescence spectrum of the composite photocatalyst of Example 2. By comparing the two, it can be seen that the intensity of the radiated light is significantly weakened after the composite photocatalyst is stimulated, indicating that the carbon layer effectively reduces the recombination of photogenerated carriers and significantly improves the problem of inherent defects of TiO2; and by comparing the red line (TC1) and the blue line (TC2), it can be seen that after increasing the amount of graphite added, within a wavelength of 400nm, the intensity of the radiated light of Example 2 is weaker than that of Example 1, which indicates that Example 2 is better in improving the inherent defects of TiO2.

[0065] Example 3

[0066] This embodiment is basically the same as Embodiment 1, except that the mass ratio of TiO2 nanoparticles to expanded graphite is 1:19.

[0067] A method for preparing a composite photocatalyst comprises the following steps:

[0068] TiO2 nanoparticles and expanded graphite were mixed in a mass ratio of 1:19 and ball-milled for 12 hours to obtain a treated product, wherein the mass ratio of small balls, medium balls and large balls used in ball milling was 6:3:1, the total weight of the grinding balls was 200 g, and the size of the ball mill was 125 mL;

[0069] The treated material was washed with deionized water for 5 times and freeze-dried to obtain a light grey powder, which is a composite photocatalyst.

[0070] Reference Figure 4 , Figure 4 The black line (TC0) is the UV-visible light absorption spectrum of pure TiO2, and the blue-green line (TC3) is the UV-visible light absorption spectrum of the composite photocatalyst of Example 3. By comparing the two, it can be seen that the light absorption of the composite photocatalyst of Example 3 in the ultraviolet region is not affected, and the absorption of visible light is significantly enhanced, which indicates that the light absorption effect of the composite photocatalyst after graphite ball milling treatment is improved; and by comparing the red line (TC1) and the green line (TC3), it can be seen that after increasing the amount of graphite added, the light absorption effect of the composite photocatalyst is not significantly increased.

[0071] Reference Figure 5 , Figure 5 The black line (TC0) is the photoluminescence spectrum of pure TiO2, and the green line (TC3) is the photoluminescence spectrum of the composite photocatalyst of Example 3. By comparing the two, it can be seen that the intensity of the radiated light is significantly weakened after the composite photocatalyst is stimulated, indicating that the carbon layer effectively reduces the recombination of photogenerated carriers and significantly improves the problem of inherent defects of TiO2; and by comparing the red line (TC1), the green line (TC3) and the blue line (TC2), it can be seen that after increasing the amount of graphite added, within a wavelength of 400nm, the intensity of the radiated light of Example 3 is the weakest, which indicates that Example 3 has the best improvement on the inherent defects of TiO2.

[0072] Example 4

[0073] A method for preparing a composite photocatalyst comprises the following steps:

[0074] TiO2 nanoparticles and expanded graphite were mixed in a mass ratio of 1:1 and ball-milled for 1 h to obtain a treated product, wherein the mass ratio of small balls, medium balls and large balls used in ball milling was 5:4:1, the total weight of the grinding balls was 200 g, and the size of the ball mill was 100 mL;

[0075] The treated material was washed with deionized water for 4 times and freeze-dried to obtain a composite photocatalyst.

[0076] Example 5

[0077] A method for preparing a composite photocatalyst comprises the following steps:

[0078] TiO2 nanoparticles and expanded graphite were mixed in a mass ratio of 1:15, and ball-milled for 20 hours to obtain a treated product, wherein the mass ratio of small balls, medium balls and large balls used in ball milling was 7:2:1, the total weight of the grinding balls was 200 g, and the size of the ball mill was 150 mL;

[0079] The treated material was washed with deionized water for three times and freeze-dried to obtain a composite photocatalyst.

[0080] Example 6

[0081] This embodiment is basically the same as the embodiment 1, except that the expanded graphite is replaced by flake graphite with a mesh size of 500 and a sheet diameter of 25 μm.

[0082] Example 7

[0083] This embodiment is basically the same as Embodiment 1, except that the expanded graphite is replaced by graphene oxide powder.

[0084] Experimental example

[0085] The photocatalytic degradation experiment was carried out on pure TiO2 and the composite photocatalysts of Examples 1-3 and 6-7, with methyl orange and rhodamine B at a concentration of 4 mg / L as simulated pollutants. The experimental results were compared with those of Figure 6-8 .

[0086] Solution preparation method: Take 4 mg of methyl orange (MO) or rhodamine B (RhB) powder, add 1000 ml of water to fully dissolve it to obtain a 4 mg / L methyl orange / rhodamine B solution.

[0087] Figure 6 The left figure is a photocatalytic degradation diagram of rhodium B, and the right figure is a photocatalytic degradation diagram of methyl orange. Among them, TC0 is the degradation curve of pure TiO2 changing with time, TC1 is the degradation curve of Example 1 changing with time, TC2 is the degradation curve of Example 2 changing with time, and TC3 is the degradation curve of Example 3 changing with time.

[0088] observe Figure 6 As can be seen from the left figure, for Rhodiola B, the time required for the degradation of pure TiO2 is 60 minutes, while the time required for the degradation of the composite photocatalyst of Example 1 is 25 minutes, and the photocatalytic efficiency of the composite photocatalyst of Example 1 has been greatly improved. And by comparing Examples 1-3, it can be seen that when the mass ratio of TiO2 nanoparticles to expanded graphite is 1:3, the photocatalytic degradation efficiency is optimal.

[0089] observe Figure 6 As can be seen from the right figure, for methyl orange, the time required for the degradation of pure TiO2 is 60 minutes, while the time required for the degradation of the composite photocatalyst of Example 1 is 25 minutes.

[0090] observe Figure 7 The catalytic reaction results show that the prepared composite catalyst has a high adsorption capacity for rhodamine B. A rhodamine B solution with a concentration of 4 mg / L can be adsorbed by nearly 90% after standing in the dark for 20 minutes, and the degradation reaction is completed within 5 minutes. Figure 7 The flake graphite / TiO2 composite catalyst also exhibits good adsorption of methyl orange (MO). After standing in the dark for 20 minutes, it can adsorb about 45% of methyl orange, but the subsequent catalytic reaction efficiency is slow. After 35 minutes of catalytic reaction, >98% of methyl orange can be degraded, which is significantly lower than the efficiency of the expanded graphite / TiO2 composite.

[0091] observe Figure 8 Compared with EG / TiO2 composite, graphene oxide (GO) / TiO2 composite has similar adsorption to rhodamine B and methyl orange, and can absorb about 10% of pollutants in the dark for 20 minutes, and the catalytic degradation efficiency is very high, and the catalytic reaction can be completed within 20 minutes. The reason may be that GO is reduced during the ball milling process, so the performance is similar to EG / TiO2.

[0092] observe Fig. 9 , from top to bottom, TC1 is the thermogravimetric analysis diagram of Example 1, TC2 is the thermogravimetric analysis diagram of Example 2, and TC3 is the thermogravimetric analysis diagram of Example 3. Fig. 9 It can be seen that when expanded graphite is used as a graphene source, the total amount of graphite on the surface of titanium dioxide particles is 1-2%.

[0093] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite photocatalyst, characterized in that: The steps include: The TiO2 particles are mixed with graphite and subjected to ball milling treatment to obtain a treated product; The treated material is washed with deionized water and dried to obtain a composite photocatalyst.

2. The method for preparing the composite photocatalyst according to claim 1, characterized in that: The size of the TiO2 particles is 10 to 50 nm.

3. The method for preparing the composite photocatalyst according to claim 1, characterized in that: The mass ratio of the TiO2 particles to the graphite is 1:(1-19).

4. The method for preparing the composite photocatalyst according to claim 1, characterized in that: The graphite is expanded graphite, flake graphite or graphene oxide.

5. The method for preparing the composite photocatalyst according to claim 1, characterized in that: The ball milling time is 1 to 20 hours.

6. The method for preparing the composite photocatalyst according to claim 1 or 5, characterized in that: Grinding balls are added during the ball milling, and the grinding balls include small balls, medium balls and large balls. The mass ratio of the small balls, medium balls and large balls is (5-7): (2-4):

1. The size of the ball milling jar used for the ball milling is 100-150mL.

7. The method for preparing the composite photocatalyst according to claim 6, characterized in that: The diameter of the large ball is 10 mm, the diameter of the medium ball is 5 mm, and the diameter of the small ball is 2.5 mm.

8. The method for preparing the composite photocatalyst according to claim 6, characterized in that: The grinding balls are made of zirconium oxide.

9. The method for preparing the composite photocatalyst according to claim 1, characterized in that: The treated material is washed with deionized water for 3 to 5 times, and the drying is freeze-drying.

10. A composite photocatalyst prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparing method for graphene / titanium dioxide photocatalyst

    CN105964236A

Cited By

  • Nanometal-graphite carbon-metal oxide composite photocatalyst and preparation method and application thereof

    CN120438011A